Corneal contact lens material with efficient drug sustained release function and preparation method
By combining hollow polydopamine nanoparticles with hydrogel polymeric monomers, corneal contact lens materials with high-efficiency drug sustained release function were prepared, which solved the problem of low drug release in the prior art and achieved a significant increase in drug loading and sustained release rate.
Patent Information
- Application Number
- CN202510078408.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
AI Technical Summary
Existing drug sustained-release contact lenses have shortcomings in drug loading capacity and sustained-release rate, resulting in low drug release.
Corneal contact lens material with high-efficiency drug sustained release function was prepared by dispersing hollow polydopamine nanoparticles in hydrogel polymerized monomers and mixing them at a specific mass ratio. This material achieves drug-loading and sustained release of the drug through the combination of specific bowl-shaped hollow polydopamine particles and hydrogel.
The drug loading and sustained release amount of the drug has been significantly improved, and the sustained release rate has been significantly improved. Compared with similar materials, the sustained release effect has been improved by 10%-20%, while not affecting other properties of the material.
Smart Images

Figure CN119868566A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of corneal contact lenses, and in particular to a corneal contact lens material with a high-efficiency drug sustained-release function and a preparation method thereof. Background Art
[0002] In recent years, with the increasing incidence of sicca conjunctivitis and bacterial conjunctivitis, people's quality of life has been greatly affected. With the trend of younger patients, the number of patients has gradually increased. How to effectively treat conjunctivitis has become an important research issue facing human society. Due to the existence of various physiological barriers, such as corneal and conjunctival barriers, tear film and rapid clearance mechanisms, the eye is a complex and challenging organ for drug delivery. Traditional topical ocular drug delivery methods (such as eye drops or ointments) usually have problems such as low utilization, poor drug absorption and the need for frequent administration, leading to a series of side effects. In contrast, drug-eluting corneal contact lenses can continuously release drugs for a longer period of time, thereby improving drug efficacy.
[0003] Corneal contact lenses are a special medical device for correcting refractive errors. They are in direct contact with the cornea and are a good drug delivery platform. Currently, the main modification methods for drug-released corneal contact lenses include electrostatic adsorption, molecular imprinting, construction of MOFs, and drug-loaded nanoparticles. For example, the Chinese invention patent with publication number CN108578059A discloses a corneal contact lens with controlled drug sustained release, which is provided with a multilayer structure of a semipermeable membrane layer, a water-absorbing swelling layer, a water-impermeable elastic membrane layer and a drug storage layer in sequence, wherein the drug storage layer is used to store the drug, and the water-absorbing swelling layer is used to release the drug. However, the problems of this technology are that the preparation of the multilayer structure is complicated and the process requirements are high; the drug loading amount of a single layer is low; and once the layers are poorly bonded, there is a risk of large-scale drug release; the Chinese invention patent with publication number CN117122559A discloses a highly oxygen-permeable corneal contact lens material with drug sustained release function, which is prepared by polymerizing hollow silica nanoparticles and hydrogel monomers to obtain a corneal contact lens material, but the sustained release drug amount is low, the lens transmittance is reduced, and the surface wettability is poor; it can be seen that this type of traditional drug sustained release corneal contact lens is still insufficient in drug loading capacity, resulting in low drug release, and therefore, it is necessary to develop a corneal contact lens material that can increase drug loading and sustained release rate. Summary of the invention
[0004] The purpose of the present invention is to solve the above technical problems and provide a drug sustained-release polymer material, which can be applied to corneal contact lens materials; the drug sustained-release polymer material can significantly increase the drug loading and drug sustained-release amount, and can achieve a higher sustained-release effect. Another purpose of the present invention is to provide the preparation and application of the drug sustained-release polymer material.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] The invention provides a drug sustained-release polymer material, wherein the drug sustained-release polymer material is obtained by dispersing hollow polydopamine nanoparticles in hydrogel polymer monomers, and mixing and polymerizing them at a mass ratio of 1-10:100; the polydopamine nanoparticles; the polydopamine nanoparticles have a particle size of 100-200nm and a wall thickness of 20-50nm.
[0007] The present invention combines amino groups on the surface of specific bowl-shaped hollow polydopamine particles, and catechol groups make it easy to combine in hydrogels. The specific bowl-shaped hollow polydopamine particles are combined with hydrogel polymer monomers of a specific mass, and the release of loaded drugs can be effectively controlled during the drug sustained release process, so as to achieve the purpose of large-scale drug loading and sustained release, and can achieve higher adsorption and sustained release amounts, and the sustained release rate is significantly improved. Compared with similar materials, the sustained release effect is improved by 10%-20%; at the same time, it does not affect the material.
[0008] Furthermore, the drug sustained-release polymer material is obtained by dispersing hollow polydopamine nanoparticles in hydrogel polymer monomers, and mixing and polymerizing them at a mass ratio of 1-5:100.
[0009] Furthermore, the polydopamine silica nanoparticles are prepared by mixing ethanol, ammonia water and water, adding tetraethyl orthosilicate (TEOS) as a silane coupling agent to hydrolyze the mixture, adding dopamine to self-polymerize the mixture after hydrolysis, and then performing a hydrothermal reaction, and etching the silicon core with an acid to obtain hollow polydopamine nanoparticles; the dosage ratio of the ethanol: ammonia water: water is 6-24:0.25-1:20-80.
[0010] The invention prepares PDA@SiO2 nanoparticles by combining the rapid condensation of tetraethyl silicate (TEOS) and the slow polymerization of dopamine under alkaline conditions, and adjusts the self-polymerization rate of dopamine by using specific amounts of ethanol, ammonia water and dopamine to prepare a uniform and stable polydopamine layer; and selectively removes silicon cores with acid to obtain the target product, bowl-shaped hollow polydopamine particles; and utilizes the uniform and stable polydopamine layer and bowl-shaped hollow polydopamine particles with a specific particle size, and combines the amino groups and catechol groups on the surface thereof to make them easy to be combined in a hydrogel, so as to achieve the purpose of large-scale drug loading.
[0011] Furthermore, the usage ratio of ethanol: ammonia water: water is 11-13: 0.4-0.6: 30-50.
[0012] Preferably, the usage ratio of ethanol:ammonia water:water is 12:0.5:40.
[0013] Furthermore, the usage ratio of ethanol: ammonia water and dopamine is 6-24:0.25-1:0.1-0.4.
[0014] Preferably, the usage ratio of ethanol:ammonia water:dopamine is 12:0.5:0.2.
[0015] Preferably, the concentration of the aqueous ammonia is 30%.
[0016] Furthermore, the usage ratio of the silane coupling agent to the dopamine is 0.25-1:0.1-0.4.
[0017] Furthermore, the dosage ratio of the silane coupling agent to the dopamine is 0.4-0.6:0.1-0.3.
[0018] Preferably, the dosage ratio of the silane coupling agent to the dopamine is 0.5:0.2.
[0019] Furthermore, the hydrothermal reaction is carried out under the following conditions: temperature of 130-150° C. and time of 12-24 h.
[0020] Preferably, the hydrothermal reaction is carried out under the following conditions: temperature is 140° C. and time is 24 h.
[0021] Furthermore, the acid used for etching the silicon core is hydrofluoric acid, and the concentration of the hydrofluoric acid is 10-30wt%.
[0022] Preferably, the hydrofluoric acid concentration is 20wt%
[0023] Furthermore, after etching the silicon core with acid, it is necessary to wash it to neutrality and vacuum dry it to remove moisture and organic impurities.
[0024] Preferably, the vacuum drying is performed at 40°C.
[0025] Furthermore, the mixed polymerization process also includes adding an initiator, and the molar ratio of the initiator to the monomer is 0.6-1%.
[0026] Preferably, the initiator is azobisisobutyronitrile or 2-hydroxy-2-methylpropiophenone.
[0027] Furthermore, the drug sustained-release polymer material is loaded with drugs by immersing the drug sustained-release polymer material in drugs, wherein the drugs are one or any combination of levofloxacin, gatifloxacin, amikacin, rebamipide, and vancomycin.
[0028] Furthermore, the monomer is pHEMA or a silicone hydrogel monomer.
[0029] Preferably, the silicone hydrogel monomer is selected from: methacryloxypropyl tris(trimethylsiloxy)silane (TRIS), γ-aminopropyl triethoxysilane (KH550) or γ-(methacryloxy)propyl trimethoxysilane (KH570) and other silicone hydrogel monomers.
[0030] The present invention provides the use of the above-mentioned drug sustained-release polymer material in the preparation of or as a corneal contact lens material.
[0031] The present invention provides a method for preparing a corneal contact lens material with a drug sustained-release function, comprising the following steps:
[0032] S1. preparing hollow polydopamine nanoparticles; mixing ethanol, ammonia and water, adding the mixture to hydrolyze the silane coupling agent, adding dopamine to self-polymerize after hydrolysis, and then performing a high-temperature hydrothermal reaction at a temperature of 130-150° C. for 12-24 h, and etching the silicon core with an acid to obtain hollow polydopamine nanoparticles;
[0033] The dosage ratio of ethanol: ammonia water: water is 6-24: 0.25-1: 20-80; the dosage ratio of dopamine is 0.4-0.6: 0.1-0.3;
[0034] S2. The hollow polydopamine nanoparticles are dispersed in the hydrogel polymer monomers, and mixed and polymerized at a mass ratio of 1-10:100 to obtain a corneal contact lens material with drug sustained-release function.
[0035] Furthermore, the self-polymerization in step S1 is carried out in a reaction system with a volume of 40-100 mL.
[0036] The beneficial effects of the present invention are as follows:
[0037] (1) The drug sustained-release polymer material of the present invention combines the amino groups on the surface of specific bowl-shaped hollow polydopamine particles, and the catechol group makes it easy to be combined in the hydrogel. The specific bowl-shaped hollow polydopamine particles are combined with a specific mass of hydrogel polymer monomers. The release of loaded drugs can be effectively controlled during the drug sustained-release process, achieving the purpose of large-scale drug loading and sustained release, and can achieve a better sustained-release effect. Compared with similar composition materials, the sustained-release effect is improved by more than 10%.
[0038] (2) The drug sustained-release polymer material of the present invention prepares PDA@SiO2 nanoparticles by combining the rapid condensation of tetraethyl silicate (TEOS) under alkaline conditions with the slow polymerization of dopamine. The self-polymerization rate of dopamine is regulated by the specific amounts of ethanol, ammonia and dopamine to prepare a uniform and stable polydopamine layer. The silicon core is selectively removed by acid to obtain the target product, bowl-shaped hollow PDA polydopamine particles. The uniform and stable polydopamine layer and bowl-shaped hollow polydopamine particles of a specific particle size are utilized, combined with the amino groups and catechol groups on their surfaces to make them easy to be combined in the hydrogel, thereby achieving the purpose of large-scale drug loading.
[0039] (3) The preparation method of the drug sustained-release polymer material of the present invention is simple, efficient, environmentally friendly, and has low requirements on equipment, and is easy to produce. The good comprehensive performance exhibited by the present invention makes it have a bright future in ophthalmic medical treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is the morphology characterization of the hollow structured polydopamine nanoparticles in Example 1 of the present invention;
[0041] Figure 1 a represents a scanning electron microscope (SEM) image; b represents a transmission electron microscope (TEM) image.
[0042] Figure 2 This is a scanning electron microscope (SEM) image of the polydopamine nanoparticles prepared in Comparative Example 1.
[0043] Figure 3 This is a schematic diagram of the structure of Example 8 under an electron microscope.
[0044] Figure 4 Schematic diagram of the sustained release of the drug in Example 1.
[0045] Figure 5 This is a schematic diagram of the sustained release of the drug in Example 2.
[0046] Figure 6 This is a schematic diagram of the sustained release of the drug in Comparative Example 1.
[0047] Figure 7 Schematic diagram of the sustained release of the drug in Comparative Example 2. DETAILED DESCRIPTION
[0048] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0049] Example 1
[0050] This embodiment provides a drug-slow-release polymer material, which can be applied to corneal contact lens materials. The preparation process is as follows:
[0051] (1) First, mix 12 mL of ethanol and 0.5 mL of 30% ammonia solution in a 100 mL beaker containing 40 mL of deionized water. After magnetic stirring for 1.0 h, add 0.5 mL of silane coupling agent tetraethyl orthosilicate TEOS dropwise into the beaker and continue stirring for 30 min. Then weigh 0.2 g of dopamine and add it to the above mixture. After stirring for 24 h, transfer it to a 100 mL reactor and perform a high-temperature hydrothermal reaction at 140 °C for 24 h. After the reactor is completely cooled, take out the reaction solution and centrifuge to obtain polydopamine particles. Wash with ethanol and pure water respectively until the supernatant is transparent. Then, place the product in 20wt% HF for etching for 2.0 h at room temperature, and wash with a large amount of pure water until the supernatant is neutral, and vacuum dry it at 40 °C to obtain the target structure nanoparticles ( Figure 1 ), the nanoparticles are hollow bowl-shaped, with a particle size between 100nm and 200nm and a wall thickness between 20nm and 50nm.
[0052] (2) preparing a hydrogel polymerization monomer solution: 200 mg of pHEMA monomer solution and 1.5 mg of azobisisobutyronitrile were mixed evenly to obtain a hydrogel polymerization monomer solution;
[0053] (3) 10 mg of the nanoparticles prepared in step (1) are dispersed in the hydrogel polymerization monomer solution of step (2), and the mixed solution is dripped into a mold after ultrasonic homogenization, and the film is degassed and pressed into a sheet, and then placed in an oven at 100° C. for curing for 6 hours, and hydrated at room temperature to obtain a hydrogel corneal contact lens material encapsulating polydopamine particles. In the lens material, the polydopamine particles account for 5% of the mass of the hydrogel matrix (mass ratio is 5:100).
[0054] Example 2
[0055] This embodiment provides a drug-slow-release polymer material, which can be applied to corneal contact lens materials. The preparation process is as follows:
[0056] The preparation was carried out in accordance with Example 1, except that the amount of initiator was adjusted to 2 mg of azobisisobutyronitrile.
[0057] Example 3
[0058] This embodiment provides a drug-slow-release polymer material, which can be applied to corneal contact lens materials. The preparation process is as follows:
[0059] The preparation was carried out in accordance with Example 1, except that the amount of initiator was adjusted to 2.5 mg of azobisisobutyronitrile.
[0060] Example 4
[0061] This embodiment provides a drug-slow-release polymer material, which can be applied to corneal contact lens materials. The preparation process is as follows:
[0062] The preparation was carried out in accordance with Example 1, except that the amount of the nanoparticles was adjusted to 15 mg; the polydopamine particles accounted for 7.5% of the mass of the hydrogel matrix (mass ratio was 7.5:100).
[0063] Example 5
[0064] This embodiment provides a drug-slow-release polymer material, which can be applied to corneal contact lens materials. The preparation process is as follows:
[0065] The preparation was carried out in accordance with Example 1, except that the amount of the nanoparticles was adjusted to 20 mg. The polydopamine particles accounted for 10% of the mass of the hydrogel matrix (mass ratio was 10:100).
[0066] Comparative Example 1
[0067] This embodiment provides a drug sustained-release polymer material, the preparation process of which is as follows:
[0068] (1) First, mix 24 mL of ethanol and 1 mL of 30% ammonia solution in a 200 mL beaker containing 80 mL of deionized water. After magnetic stirring for 1.0 h, add 1 mL of TEOS dropwise into the beaker and continue stirring for 30 min. Then weigh 0.4 g of dopamine and add it to the above mixture. After stirring for 24 h, transfer it to a 200 mL reactor and perform a high-temperature hydrothermal reaction at 140 °C for 24 h. After the reactor is completely cooled, take out the reaction solution and centrifuge to obtain polydopamine particles. Wash with ethanol and pure water respectively until the supernatant is transparent. Then, etch the product in 20 wt% HF at room temperature for 2.0 h, and wash with a large amount of pure water until the supernatant is neutral. Vacuum dry it at 40 °C to obtain the target nanoparticles (such as Figure 2 ).
[0069] (2) preparing a hydrogel polymerization monomer solution: 200 mg of pHEMA monomer solution and 1.5 mg of azobisisobutyronitrile were mixed evenly to obtain a hydrogel polymerization monomer solution;
[0070] (3) 10 mg of the nanoparticles prepared in step (1) are dispersed in the hydrogel polymerization monomer solution of step (2), and the mixed solution is dripped into a mold after being homogenized by ultrasound. After degassing and pressing into a film, the film is placed in an oven at 100° C. for curing for 6 hours, and polymerized at room temperature to obtain a hydrogel corneal contact lens material encapsulating polydopamine particles. In the lens material, the polydopamine particles account for 5% of the mass of the hydrogel matrix.
[0071] Embodiment 6-7
[0072] This embodiment provides a drug sustained-release polymer material, the preparation process of which is as follows:
[0073] The preparation method is the same as that of Example 1, except that in step (1), the hollow polydopamine nanoparticles are dispersed in the hydrogel polymer monomer, and the specific ratios are 1:100 and 2:100, respectively. The other steps are the same as those of Example 1.
[0074] Comparative Example 2
[0075] This embodiment provides a drug sustained-release polymer material, the preparation process of which is as follows:
[0076] The preparation of the hydrogel material was the same as in Example 1, except that no polydopamine particles were added.
[0077] Embodiment 8-11
[0078] The preparation process of each drug sustained-release polymer material provided in this embodiment is as follows:
[0079] Referring to Example 1, only the ratio of ethanol: ammonia water: deionized water was changed to 6:0.25:20, specifically 6 mL of ethanol; 0.25 mL of ammonia water; and 20 mL of deionized water. The other steps were the same as those in Example 1, and the prepared sample material was used as Example 8.
[0080] Referring to Example 1, only the ratio of ethanol: ammonia water: deionized water was changed to 12:0.5:80, specifically 12 mL of ethanol; 0.5 mL of ammonia water; and 80 mL of deionized water. The other steps were the same as those in Example 1, and the sample material prepared was used as Example 9.
[0081] Referring to Example 1, only the ratio of ethanol: ammonia water: deionized water was changed to 12:0.25:20, specifically 12 mL of ethanol; 0.25 mL of ammonia water; and 20 mL of deionized water. The other steps were the same as those in Example 1, and the sample material prepared was used as Example 10.
[0082] Referring to Example 1, only the ratio of ethanol: ammonia water: deionized water was changed to 12:0.25:40, specifically 12 mL of ethanol; 0.25 mL of ammonia water; and 40 mL of deionized water. The other steps were the same as those in Example 1, and the sample material prepared was used as Example 11.
[0083] Examples 12-15
[0084] The preparation process of each drug sustained-release polymer material provided in this embodiment is as follows:
[0085] Referring to Example 1, the ratio of the silane coupling agent to the dopamine is 0.25:0.1, specifically 0.25 mL of tetraethyl orthosilicate and 0.1 g of dopamine. The other steps are the same as those in Example 1, and the prepared sample material is used as Example 12.
[0086] Referring to Example 1, the ratio of the silane coupling agent to the dopamine is 0.5:0.1, specifically 0.5 mL of tetraethyl orthosilicate and 0.1 g of dopamine. The other steps are the same as those in Example 1, and the prepared sample material is used as Example 13.
[0087] Referring to Example 1, the ratio of the silane coupling agent to the dopamine is 0.5:0.4, specifically 0.5 mL of tetraethyl orthosilicate and 0.4 g of dopamine. The other steps are the same as those in Example 1, and the prepared sample material is used as Example 14.
[0088] Referring to Example 1, the ratio of the silane coupling agent to the dopamine is 1:0.4. Specifically, tetraethyl orthosilicate 1
[0089] mL, dopamine 0.4 g, and other steps are the same as in Example 1 to prepare the sample material as Example 15.
[0090] Example 16
[0091] (1) The same as step (1) of Example 1 is used to prepare nanoparticles.
[0092] (2) Preparation of silicone hydrogel polymerization monomer solution: 200 mg of γ-(methacryloxy)propyl trimethoxysilane (KH570) monomer solution and 1.5 mg of 2-hydroxy-2-methylpropiophenone were mixed to obtain a silicone hydrogel polymerization monomer solution. In this embodiment, the silicone hydrogel monomer is preferably methacryloxypropyl tri(trimethylsiloxy)silane (TRIS).
[0093] (3) 10 mg of the nanoparticles prepared in step (1) were dispersed in the silicone hydrogel polymerization monomer solution in step (2), and the mixed solution was dripped into a mold after ultrasonic homogenization. After degassing and pressing into a film, it was placed under a light intensity of 365 nm and 10 mV / cm 2 The polydopamine particles are encapsulated in a silicone hydrogel contact lens material, and the polydopamine particles account for 5% of the mass of the silicone hydrogel matrix.
[0094] Experimental Example 1 Characterization Test
[0095] (1) Characterization methods
[0096] The morphology, size and internal structure of the bowl-shaped hollow polydopamine nanoparticles in Experimental Example 1 and Comparative Example 1 were characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM), respectively, and the same tests were performed on the above Examples 2-16 and Comparative Example 2.
[0097] (2) Characterization results
[0098] pass Figure 1 In a, it is concluded that the size of the polydopamine nanoparticles (PDA particles) of Experimental Example 1 is approximately 100-200 nm, the size is relatively uniform, and there is no agglomeration phenomenon; Figure 1 From b, we can see that the particle wall thickness is about 20-50nm and the structure is stable. Figure 2 The PDA particles in Comparative Example 1 show that the polydopamine particles in this comparative example are not uniformly aggregated, the particles are broken and agglomerated. The polydopamine particles in Experimental Examples 8-15 all failed to form bowl-shaped hollow particles. The fiber structure of Example 8 is as follows: Figure 3 As shown, it can be seen that its structure is not a bowl-shaped hollow particle morphology, and has agglomeration phenomenon similar to the synthetic particles in Comparative Example 1.
[0099] Experimental Example 2 Adsorption-sustained release test
[0100] 1. Experimental Procedure
[0101] (1) First, a 1% levofloxacin glacial acetic acid solution with a concentration of 0.2 mg / mL was prepared; 10.0 mg of the hydrogel contact lens material encapsulating nanoparticles obtained in Examples 1-7, Example 16 and Comparative Example 1 was placed in a centrifuge tube containing 10 mL of the above-prepared solution (pH=7.4), and the mixture was fully shaken at room temperature for 6 h. After reaching adsorption equilibrium, a quantitatively diluted levofloxacin solution was taken to measure its ultraviolet absorbance.
[0102] (2) Standard curve determination: Weigh 5 mg of levofloxacin powder, dissolve it with an appropriate amount of 1% glacial acetic acid, and then dilute it to volume with a 50 mL volumetric flask. Then, measure 10 μL, 20 μL, 50 μL, 100 μL, 150 μL, and 200 μL of levofloxacin solution and dilute it to volume with a 10 mL volumetric flask. After preparing the standard solution, use an ultraviolet spectrophotometer to measure the absorbance at the maximum wavelength and draw a standard curve.
[0103] (3) The adsorbed material was then placed in 10 mL of simulated tear fluid, and the tear fluid was changed every 1 h. The drug concentration in the tear fluid was measured after each change. The material was taken out after 6 h, the drug concentration in the solution was measured, and the sustained-release amount of the drug was calculated.
[0104] 2. Experimental results
[0105] The test results are shown in Table 1 and Figure 4-7 It can be seen that the adsorption-sustained release amount of the corneal contact lens material without adding polydopamine nanoparticles is very small, and the conditions of Examples 1-7 all have better effects, especially the adsorption-sustained release amount of the hydrogel corneal lens material coated with polydopamine particles in Example 1 is the best, and the sustained release rate also reaches 84%. Example 16 shows that the same is applicable to silicone hydrogel monomers.
[0106] Table 1 Drug adsorption and release of Examples 1-7 and 16 and Comparative Examples 1-2
[0107] sample Adsorption amount (μg) Sustained release amount (μg) Sustained release rate Example 1 50 42 84% Example 2 37 23 62% Example 3 38 25 66% Example 4 42 29 69% Example 5 44 31 70% Comparative Example 1 32 20 63% Example 6 31 26 83% Example 7 33 27 82% Comparative Example 2 10 7 70% Example 8 30 23 77% Example 9 32 25 78% Example 10 31 23 74% Embodiment 11 32 24 75% Example 12 26 20 77% Example 13 25 18 72% Embodiment 14 36 26 72% Embodiment 15 34 25 74% Example 16 49 41 83%
[0108] Experimental Example 3 Transparency, oxygen permeability, moisture content, etc. tests
[0109] 1. Experimental Methods
[0110] In this experimental example, according to the adsorption-sustained release results, the materials in Examples 1-7, Example 16 and Comparative Examples 1-2 were tested for contact angle, oxygen permeability and light transmittance, so as to test the feasibility of application in corneal contact lenses as well as their wettability, comfort, optical properties and oxygen permeability.
[0111] 2. Experimental results
[0112] The test results are shown in Table 2. There is no significant change in the surface contact angle between Examples 1-7 and Example 16 and Comparative Examples 1-2. The addition of polydopamine particles has a slight effect on the transmittance, but due to the small amount of addition, the transmittance of Example 1 is still above 90%, which meets the optical performance requirements of corneal contact lens products. In addition, the oxygen permeability of the material loaded with PDA particles is also increased by nearly 50%. It can be seen that the application of the drug sustained-release polymer material in corneal contact lens materials will not have an adverse effect on its optical properties, but on the contrary will improve its oxygen permeability and wettability.
[0113] Table 2 Contact angle, light transmittance and oxygen permeability test of Examples 1-7, Example 16 and Comparative Examples 1-2
[0114] Example Contact angle (°) Light transmittance (%) Oxygen permeability Example 1 38 92 40 Example 2 43 90 38 Example 3 41 91 36 Example 4 42 87 37 Example 5 40 83 35 Comparative Example 1 44 89 30 Example 6 42 94 32 Example 7 41 93 33 Comparative Example 2 43 95 22 Example 16 40 90 90
[0115] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the solution. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents based on the understanding of the present solution without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A drug sustained-release polymer material, characterized in that: The drug sustained-release polymer material is obtained by dispersing hollow polydopamine nanoparticles in hydrogel polymer monomers, and mixing and polymerizing them at a mass ratio of 1-10:100; the particle size of the polydopamine nanoparticles is 100-200nm, and the wall thickness is 20-50nm.
2. The drug sustained-release polymer material according to claim 1, characterized in that: The polydopamine silicon dioxide nanoparticles are prepared by mixing ethanol, ammonia water and water, adding tetraethyl orthosilicate as a silane coupling agent to hydrolyze it, adding dopamine after hydrolysis to self-polymerize, then performing a hydrothermal reaction, and etching the silicon core with acid to obtain hollow polydopamine nanoparticles; the dosage ratio of the ethanol: ammonia water: water is 6-24: 0.25-1: 20-80.
3. The drug sustained-release polymer material according to claim 1, characterized in that: The dosage ratio of the ethanol: ammonia water and dopamine is 6-24: 0.25-1:0.1-0.4。 4. The drug sustained-release polymer material according to claim 1, characterized in that: The dosage ratio of the silane coupling agent to the dopamine is 0.25-1.0:0.1-0.
4.
5. The drug sustained-release polymer material according to claim 1, characterized in that: The acid used for etching the silicon core is hydrofluoric acid, and the concentration of the hydrofluoric acid is 10-30wt%.
6. The drug sustained-release polymer material according to claim 1, characterized in that: The mixed polymerization process also includes adding an initiator, wherein the molar ratio of the initiator to the monomer is 0.6-1%.
7. The drug sustained-release polymer material according to claim 1, characterized in that: The drug loading of the drug sustained-release polymer material is achieved by soaking the drug sustained-release polymer material in the drug, wherein the drug is one or any combination of levofloxacin, gatifloxacin, amikacin, rebamipide and vancomycin.
8. The drug sustained-release polymer material according to claim 1, characterized in that: The monomer is pHEMA or a silicone hydrogel monomer.
9. Use of the drug sustained-release polymer material according to any one of claims 1 to 8 in the preparation of or as a corneal contact lens material.
10. A method for preparing a corneal contact lens material with drug sustained-release function, characterized in that: The steps include: S1. preparing hollow polydopamine nanoparticles; mixing ethanol, ammonia and water, adding the mixture to hydrolyze the silane coupling agent, adding dopamine to self-polymerize after hydrolysis, and then performing a high-temperature hydrothermal reaction at a temperature of 130-150° C. for 12-24 h, and etching the silicon core with an acid to obtain hollow polydopamine nanoparticles; The dosage ratio of ethanol: ammonia water: water is 6-24: 0.25-1: 20-80; the dosage ratio of dopamine is 0.4-0.6: 0.1-0.3; S2. The hollow polydopamine nanoparticles are dispersed in the hydrogel polymer monomers, and mixed and polymerized at a mass ratio of 1-10:100 to obtain a corneal contact lens material with drug sustained-release function.
Citation Information
Patent Citations
Corneal contact lens achieving controlled drug release
CN108578059A
High-oxygen-permeability corneal contact lens material with drug sustained-release function and preparation method of high-oxygen-permeability corneal contact lens material
CN117122559A
Cited By
In-situ drug-loading hydrogel based on nano-bottle packaging technology as well as preparation method and application of in-situ drug-loading hydrogel
CN121197040A